Chronic bacterial infection activates autoreactive B cells and induces isotype switching and autoantigen‐driven mutations. Issue 1 (16th November 2015) - Jung, Sophie; Schickel, Jean‐Nicolas; Kern, Aurélie; Knapp, Anne‐Marie; Eftekhari, Pierre; Da Silva, Sylvia; Jaulhac, Benoît; Brink, Robert; Soulas‐Sprauel, Pauline; Pasquali, Jean‐Louis; Martin, Thierry; Korganow, Anne‐Sophie
Abstract : The links between infections and the development of B‐cell‐mediated autoimmune diseases are still unclear. In particular, it has been suggested that infection‐induced stimulation of innate immune sensors can engage low affinity autoreactive B lymphocytes to mature and produce mutated IgG pathogenic autoantibodies. To test this hypothesis, we established a new knock‐in mouse model in which autoreactive B cells could be committed to an affinity maturation process. We show that a chronic bacterial infection allows the activation of such B cells and the production of nonmutated IgM autoantibodies. Moreover, in the constitutive presence of their soluble antigen, some autoreactive clones are able to acquire a germinal center phenotype, to induce Aicda gene expression and to introduce somatic mutations in the IgG heavy chain variable region on amino acids forming direct contacts with the autoantigen. Paradoxically, only lower affinity variants are detected, which strongly suggests that higher affinity autoantibodies secreting B cells are counterselected. For the first time, we demonstrate in vivo that a noncross‐reactive infectious agent can activate and induce autoreactive B cells to isotype switching and autoantigen‐driven mutations, but on a nonautoimmune background, tolerance mechanisms prevent the formation of consequently dangerous autoimmunity.